Racismo no futebol brasileiro: a ótica do jogador negro - Pereira, Igor Moreira Dias (2021)
The present research had as main objective to understand the meaning of racist acts for players and former black players of Brazilian professional soccer who have already suffered this violence, or not, in a soccer match. The applied methodology used qualitative research methods and data collection took place through semi-structured interviews. In this sense, open questions provided greater freedom of answers by respondents. The understanding of racist acts from the point of view of black players and ex-players who work in Brazilian football, became the research problem. Therefore, it was necessary to build a theoretical framework that would contribute to the achievement of this long path, which started with the concepts of biopower pointed out by Foucault and necropolitics in the conception of Mbembe, 2016, entering into the scope of racism and its elements, prejudice and discrimination. a piece of the history of blacks in Brazil was also approached, thought from the perspective of the “myth of racial democracy”, and the myth was taken up again from the narratives of those surveyed, as well as other manifestations of racism, among them: the scientific, the whitening process, institutional and structural racisms. As final considerations we have that the players and former players surveyed in general, recognize racism both on and off the field, but sometimes deny or try to alleviate these issues, which can be a form of defense in relation to the pain suffered through racial violence. However, the meaning of racist acts on the football field, transits over the understanding that this action aims at destabilizing the player, as well as, the manifestation of racial violence in football comes from racist people. Finally, based on the players' certain fear of addressing the racial issue, it is also considered the relevance of the discussions of racial agendas in all sectors of society, in order to raise awareness among whites and blacks to face racism